Enhanced bed shear stress and mixing in the tidal wake of an offshore wind turbine monopile - M. J. Austin; C. A. Unsworth; K. J. J. Van Landeghem; B. J. Lincoln (Ocean Science)
Tidal flow past offshore wind farm (OWF) infrastructure generates a turbulent vortex wake. The wake is hypothesised to enhance seabed stress and water column turbulence mixing, thereby affecting seabed mobility, water column stratification and the transport of nutrients and oxygen and resulting in ecological impacts. We collect novel hydrodynamic data 40 m from an OWF monopile over a spring–neap cycle and use high-frequency velocity measurements to quantify turbulence. Outside of the wake, we observe a classical depth-limited boundary layer, with strong turbulence production and dissipation forced by tidal shear at the seabed. Inside the wake, turbulence production, dissipation and stress are enhanced throughout the full water column and are maximised in the upper half of the water column, where they correspond to a strong mean velocity deficit. Our results show that the seabed drag coefficient is doubled from Cd=3.5×10-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="76pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="edfc0f85dab2553f696e0a9ccc20d686"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="os-21-81-2025-ie00001.svg" width="76pt" height="16pt" src="os-21-81-2025-ie00001.png"/></svg:svg> to 7.8×10-3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="51pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="716867e7e7cfcce15dee278550562b0e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="os-21-81-2025-ie00002.svg" width="51pt" height="14pt" src="os-21-81-2025-ie00002.png"/></svg:svg>, suggesting greater seabed mobility, and the eddy viscosity is increased by 1 order of magnitude, indicating enhanced water column mixing. This research provides some valuable insight as OWFs expand into deeper seasonally stratified waters using both bottom-fixed and floating structures, where the addition of enhanced wake turbulence may have broad impacts as the additional mixing energy is added to regions with low rates of background mixing.